Implementasi Teori Konsep Ida Jean Orlando Dalam Pemberian Asuhan Keperawatan Pada Pasien Fraktur Humerus - Fenny Maryani; Irna Nursanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Background: Fractures can occur in all bones, one of which is a humerus fracture. Humerus fracture is a fracture of the longest and largest bone of the superior extremity caused by direct or indirect impact or trauma. Ida Jean Orlando, is a first generation Irish-American who was born on August 12, 1926 in New Jersey. Ida Jean Orlando's concept model is known as The Discipline and Teaching of Nursing Process: An Evaluative Study”. Ida Jean Orlando first published her theory in "The Dynamic nurse-patient relationship: Function, process and principles of Professional Nursing Practice" (1961) and published her second book entitled; “The Discipline and Teaching of Nursing Process: An Evaluative Study (1972). Orlando made several important contributions to nursing theory and practice. The concept of the nursing process that he provides includes several criteria, including providing a relationship concept that is described systematically regarding phenomena in the field of nursing, specifying the relationship between nursing concepts, explaining what happens during the nursing process and why it happens, describing how nursing phenomena can be controlled and explains how to control to predict the outcome of the nursing process.Objective: This research aims to implement nursing care for Humerus Fracture patients using the Ida Jean Orlando concept model approach. Research methodology: This research uses a Case Study, namely providing nursing care to patients with Humerus Fractures. Results: The results of this research are to improve nurse-patient interactions, a better understanding of relationship dynamics in the nursing process, and their impact on overall patient outcomes.Conclusion:The conclusion of this research is that the application of nursing care to Humerus Fracture patients using the Ida Jean Orlando concept model approach can make a positive contribution to nurse-patient interactions and overall patient outcomes.